2012
DOI: 10.5713/ajas.2011.11377
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Immune Stress on Performance Parameters, Intestinal Enzyme Activity and mRNA Expression of Intestinal Transporters in Broiler Chickens

Abstract: Immune stress is the loss of immune homeostasis caused by external forces. The purpose of this experiment was to investigate the effects of immune stress on the growth performance, small intestinal enzymes and peristalsis rate, and mRNA expression of nutrient transporters in broiler chickens. Four hundred and thirty-two 1-d-old broilers (Cobb500) were randomly assigned to four groups for treatment; each group included nine cages with 12 birds per cage. Group 1 = no vaccine (NV); Group 2 = conventional vaccine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 39 publications
1
16
0
8
Order By: Relevance
“…Etsumori (1991) reported that both cold-exposed rats and fasted rats showed a decreased amylase activity. Other studies, however, reported that thermal-stressed birds had a higher enzymatic activity (Feng et al, 2012;Routman, Yoshida, Frizzas De Lima, Macari, & Pizauro, 2003). The current research demonstrated that immune stress on chickens significantly decreased amylase activity in jejunum, which affected the energy utilisation negatively and resulted in depression on growth performance in broiler chickens.…”
Section: Food and Agricultural Immunologymentioning
confidence: 43%
See 2 more Smart Citations
“…Etsumori (1991) reported that both cold-exposed rats and fasted rats showed a decreased amylase activity. Other studies, however, reported that thermal-stressed birds had a higher enzymatic activity (Feng et al, 2012;Routman, Yoshida, Frizzas De Lima, Macari, & Pizauro, 2003). The current research demonstrated that immune stress on chickens significantly decreased amylase activity in jejunum, which affected the energy utilisation negatively and resulted in depression on growth performance in broiler chickens.…”
Section: Food and Agricultural Immunologymentioning
confidence: 43%
“…199 Decuypere, & Buyse, 2004;Star, Kemp, van den Anker, & Parmentier, 2008;Virden et al, 2007). These decreases may be explained according to which immune stress is the immunomodulator and reallocates nutrients to immune response (Feng et al, 2012). However, effects of stress on FCR were reported inconsistently in poultry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cause was attributed to be heat stress which disturbs the balance of intestinal bacteria and hence, reduces nutrient digestibility and absorption (Feng et al . ). Contrarily, at the end of the experimental period, broilers fed on betaine‐supplemented diet had a higher growth performance and lower FGR, although the results of several other studies revealed minimal or no effect of betaine supplementation on animal performance (Zulkifli et al .…”
Section: Discussionmentioning
confidence: 97%
“…Esto puede implicar incomodidad o incluso dolor para los animales, lo cual puede generar estrés y, por consiguiente, cambios comportamentales y fisiológicos que conllevan a la disminución de su bienestar (Mellor et El estrés es una respuesta inespecífica del organismo animal ante condiciones ambientales adversas que produce ajustes fisiológicos y metabólicos para mantener la homeostasis, genera efectos sobre el sistema nervioso central, el sistema neuroendocrino y el sistema inmune (Sordillo y Aitken, 2008;Feng et al, 2012). En la respuesta neuroendocrina al estrés, el hipotálamo libera el factor liberador de corticotropina, arginina vasopresina, péptidos derivados de la propiomelanocortina, β endorfinas y las hormonas catabólicas (catecoloaminas y glucocorticoides) que participan de forma adversa con las hormonas anabólicas (hormona de crecimiento y hormonas gonadales), activando respuestas adaptativas para la sobrevivencia (Charmandari et al, 2005).…”
Section: Introductionunclassified